Visions and decisions imagination and technique in music composition - Adolphe, Bruce 1955- (Cambridge elements, 2023)
Investigates the balance and interaction of imagination (visions) and technique (decisions) in the composition of music. It examines how works start from visions in a range of music, comparing musical ideas and techniques to models in other creative disciplines